Transmission of Bulk Power from DC-Based Offshore Wind Farm to Grid Through HVDC System - Muyeen, S.M.; Al-Durra, A.; Tamura, J. (2012)
Trends in growth of the wind energy is getting additional pace by offshore technology. This chapter investigates a suitable control strategy for a DC-based offshore wind farm to transmit bulk power to an onshore grid through a high voltage DC (HVDC) transmission line. The offshore wind farm is composed of variable-speed wind turbines driving permanent magnet synchronous generators (PMSG). Each PMSG is connected to the DC bus through a generator-side converter unit to ensure maximum power point tracking control. The DC voltage of the DC-bus is stepped up using a full-bridge DC-DC converter at the offshore HVDC station, and the wind farm output power is transmitted through the HVDC cable. The onshore HVDC station converts the DC voltage to a suitable AC grid voltage. Detailed modeling and control strategies of the overall system are presented. Real wind speed data is used in the simulation study to obtain a realistic response. The effectiveness of the coordinated control strategy developed for the proposed system is verified by simulation analyses using PSCAD/EMTDC, which is the standard power system software package.